2020
DOI: 10.3847/2041-8213/ab7932
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Change in X-Ray Variability and a Jet Ejection in the Black Hole Transient MAXI J1820+070

Abstract: We present Neutron Star Interior Composition Explorer X-ray and Arcminute Microkelvin Imager Large Array radio observations of a rapid hard-to-soft state transition in the black hole X-ray transient MAXI J1820+070. During the transition from the hard state to the soft state a switch between two particular types of quasiperiodic oscillations (QPOs) was seen in the X-ray power density spectra, from type-C to type-B, along with a drop in the strength of the broadband X-ray variability and a brief flare in the 7-1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
126
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(134 citation statements)
references
References 36 publications
8
126
0
Order By: Relevance
“…The NuSTAR data from the initial hard state are analysed in Buisson et al (2019), showing that the evolution is governed by changes in coronal rather than disc geometry, agreeing with the trend in reverberation lags seen in NICER data (Kara et al 2019). Several phenomena during the transition have already been reported, including a bipolar radio plasma ejection (Bright et al 2020) and a type B QPO (Homan et al 2020). The jet ejecta were also observed in X-rays (Espinasse et al 2020).…”
Section: Maxi J1820+070supporting
confidence: 71%
See 1 more Smart Citation
“…The NuSTAR data from the initial hard state are analysed in Buisson et al (2019), showing that the evolution is governed by changes in coronal rather than disc geometry, agreeing with the trend in reverberation lags seen in NICER data (Kara et al 2019). Several phenomena during the transition have already been reported, including a bipolar radio plasma ejection (Bright et al 2020) and a type B QPO (Homan et al 2020). The jet ejecta were also observed in X-rays (Espinasse et al 2020).…”
Section: Maxi J1820+070supporting
confidence: 71%
“…The variability in MAXI J1820+070 analysed here occurs close to but distinct in time to several other features in the state change. There may be some association with the jet: around 1 day before the flaring variability, there is a jet ejection coincident with a type B QPO (Bright et al 2020;Espinasse et al 2020;Homan et al 2020). The flaring is too late to be directly associated with the ejection but could represent settling from the post-ejection state to an equilibrium.…”
Section: Discussionmentioning
confidence: 99%
“…MAXI J1820+070 is one of the brightest BHBs detected so far, and has exhibited a great amount of activity in radio (Bright et al 2020;Homan et al 2020), NIR (Sánchez-Sierras & Muñoz-Darias 2020), optical (Muñoz-Darias et al 2019;Paice et al 2019;Shidatsu et al 2019;Veledina et al 2019), ultraviolet (UV; Kajava et al 2019), and X-ray (Buisson et al 2019;Kara et al 2019;Espinasse et al 2020;Wang et al 2020b;Buisson et al 2021;You et al 2021;Zdziarski et al 2021). In the hard state, reverberation analysis using the Neutron Star Interior Composition Interior Explorer (NICER; Gendreau et al 2016) showed that while the broad iron line profile remained constant (and only the narrow component decreased), the frequency range where the (soft) reverberation lag dominated increased (Kara et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis has been later confirmed by reflection spectroscopy in the context of a dual-lamppost, where the height of the upper lamppost decreased while the lower one stayed constant (Buisson et al 2019), and by the increase of the peak frequency of the quasi-periodic oscillations (QPOs; Ingram & Motta 2019). During the hard-to-soft transition, an extremely powerful superluminal ejection was observed in the radio band (Bright et al 2020) very close in time with a small flare in the 7-12 keV band and a transition from type-C to type-B QPO (Homan et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Fabian et al 2020). During the state transition, a change on the type of X-ray quasi-periodic oscillations was observed and immediately followed by the launch of a relativistic jet (Homan et al 2020;.…”
Section: Introductionmentioning
confidence: 99%